Neutropenia and viral load decline during treatment of hepatitis C virus genotype-4 - Amer, Aliaa; Shebl, Fatma; Derbala, Moutaz (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Neutrophil count and magnitude of decrease from baseline are not correlated with infection rate in recipients of interferon-based therapy for hepatitis C (HCV). The association of neutropenia with viral response raises the potential dilemma of trying to maintain patients on therapy despite adverse events. We studied the relationship between early viral clearance in response to treatment, and neutrophil count and fall in neutrophils in HCV-genotype 4 patients. Materials and Methods: Two-hundred and one patients with HCV-genotype 4 were enrolled. Results: Rapid and early virological responses (RVR and EVR) were achieved in 33.3% and 61.5% respectively. None of the patients developed symptomatic infection regardless of the degree of neutrophil decline. Neutrophil decline at week 2 significantly correlated with viral load at week 12 (r=0.40, p=0.042), and neutrophil decline at week 4 significantly correlated with viral load decline at week 12 (r=0.21, p=0.006). Using logistic regression, pretreatment neutrophil count significantly predicted RVR and EVR, such that individuals who achieved RVR and EVR had higher pretreatment neutrophils compared to non-responders (X2= 4.94, p=0.026; X2=7.67, p=0.005 respectively). Adjusting for age, sex, grade, fibrosis, and pretreatment neutropenia; decline in neutrophil count was significantly associated with lower viral load over time (t=-2.27, p=0.027) and higher viral load decline over time (t=2.73, p=0.009) and achieving EVR (t=2.04, p=0.044). Conclusion: In genotype 4 patients, neutropenia can be a predictor of response. Neutropenia may reflect disappearance of genomic hepatitis C viral RNA from mononuclear cells. The relationship between neutropenia and response is confined to the first 12 weeks of therapy.